2008
DOI: 10.4103/0973-6131.36795
|View full text |Cite
|
Sign up to set email alerts
|

Influence of yoga on postoperative outcomes and wound healing in early operable breast cancer patients undergoing surgery

Abstract: Context:Pre- and postoperative distress in breast cancer patients can cause complications and delay recovery from surgery.Objective:The aim of our study was to evaluate the effects of yoga intervention on postoperative outcomes and wound healing in early operable breast cancer patients undergoing surgery.Methods:Ninety-eight recently diagnosed stage II and III breast cancer patients were recruited in a randomized controlled trial comparing the effects of a yoga program with supportive therapy and exercise reha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…Six studies delivered yoga in group classes [38, 41-42, 44-47, 57], five in one-on-one sessions [40, 43, 48-52, 54-56, 58], and two did not specify the format [36, 39]. Most (9 of 13) provided audio or printed materials for home practice.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies delivered yoga in group classes [38, 41-42, 44-47, 57], five in one-on-one sessions [40, 43, 48-52, 54-56, 58], and two did not specify the format [36, 39]. Most (9 of 13) provided audio or printed materials for home practice.…”
Section: Resultsmentioning
confidence: 99%
“…In studies with sufficient information to compare, attrition was greater among yoga participants in two studies [37, 47], among control participants in three studies [38, 48-49, 51-52, 54-56], and approximately equal across groups in four studies [41-43, 58]. Two trials reported 100% completion [39, 57].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations